2006
DOI: 10.1073/pnas.0508313103
|View full text |Cite
|
Sign up to set email alerts
|

Lamprey type II collagen and Sox9 reveal an ancient origin of the vertebrate collagenous skeleton

Abstract: Type II collagen is the major cartilage matrix protein in the jawed vertebrate skeleton. Lampreys and hagfishes, by contrast, are thought to have noncollagenous cartilage. This difference in skeletal structure has led to the hypothesis that the vertebrate common ancestor had a noncollagenous skeleton, with type II collagen becoming the predominant cartilage matrix protein after the divergence of jawless fish from the jawed vertebrates Ϸ500 million years ago. Here we report that lampreys have two type II collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 44 publications
(49 reference statements)
5
81
0
Order By: Relevance
“…However, recent studies have shown that lamprey embryos do express type II collagen in pharyngeal cartilage, and that collagen expression is dependent on the express ion of the up stream transcription factor SaxE (McCauley and Bronner-Fraser, 2006;Zhang et al ., 2006 ). Now, similar overlapping expression patterns have been shown for hemichordates with a fibrillar collagen and SaxE , indicating that this shallow gene network has been conserved in the formation of pharyngeal cartilage since the stem deu terostomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have shown that lamprey embryos do express type II collagen in pharyngeal cartilage, and that collagen expression is dependent on the express ion of the up stream transcription factor SaxE (McCauley and Bronner-Fraser, 2006;Zhang et al ., 2006 ). Now, similar overlapping expression patterns have been shown for hemichordates with a fibrillar collagen and SaxE , indicating that this shallow gene network has been conserved in the formation of pharyngeal cartilage since the stem deu terostomes.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of these genes is often overlapping and there is some, but not total functional redundancy between Sox8, Sox9, and SoxlO (Kellerer et a1., 2006;O'Donnell et al ., 2006 ). In vertebrates-both agnathans and gnathostomes-pharyngeal cartilage development is characterized by the early expression of Sox9 in the neural crest cells that migrate into the pharyngeal pouches (Yan et al, 2002;McCauley and Bronner-Fraser, 2006;Zhang et al, 2006). Sox9 is responsible for directly activating transcription of several genes coding for proteins that compose vertebrate cartilage ECM .…”
mentioning
confidence: 99%
“…The strategy of using numerous short sequences in the Petromyzon marinus Trace Archive together with the two partially assembled genomes should be applicable for studies already under way for other vertebrate systems, including, for example, the evolution of complement systems (Kimura et al 2009), the extracellular matrix (Hynes 2012;Adams et al 2015), bone formation (Zhang et al 2006), and numerous other systems that have been expanded by gene duplications during the course of vertebrate evolution. In a sense, the use of this approach allows one to make use of information discarded during the assembly process.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have begun to shed light on the molecular mechanisms that regulate chondrogenesis in lampreys (McCauley and BronnerFraser, 2006;Zhang et al, 2006;Ohtani et al, 2008;McCauley, 2008). It has been demonstrated that the major extracellular matrix (ECM) protein of the lamprey piston (tongue), annular (mouth), neurocranial, and trabecular cartilage in lampreys is lamprin, an elastin-like protein that is unique to lampreys (McBurney et al, 1996a;McBurney and Wright, 1996;Wright et al, 1983) but lamprin was not detected in branchial or pericardial cartilage (McBurney et al, 1996b).…”
Section: Developmental Dynamicsmentioning
confidence: 99%